ESTABLISHING FINE-GRAINED SEDIMENT BUDGETS FOR THE PANG AND LAMBOURN LOCAR CATCHMENTS, UK - Walling D.E.; Collins A.L.; Jones P.A.; Leeks G.J.L.; Old G. (My University, 2006)
An integrated approach to data collection, combining the use of 137Cs measurements, sediment source fingerprinting, bed sediment surveys and conventional river monitoring, has been successfully employed to establish the fine-grained sediment budgets of two lowland groundwater-fed catchments in the UK. Gross surface erosion is higher on cultivated land (Pang: 55 263 t yr-1 or 507 t km-2 yr-1; Lambourn: 79 997 t yr-1 or 437 t km-2 yr-1) than on pasture (Pang: 1960 t yr-1 or 140 t km-2 yr-1; Lambourn: 1425 t yr-1 or 95 t km-2 yr-1) in both study areas and a substantial proportion of the mobilized sediment is sequestered within the fields (Pang: 28 058 t yr-1 or 228 t km-2 yr-1; Lambourn: 55 575 t yr-1 or 281 t km-2 yr-1) and between the individual fields and the river channel network (Pang: 28 672 t yr-1 or 233 t km-2 yr-1; Lambourn: 24 782 t yr-1 or 125 t km-2 yr-1). The sediment contribution from banks and subsurface sources is relatively low and typically ca. 5 t yr-1 in the Pang and ca. 11 t yr-1 in the Lambourn, representing only about 1% of the suspended sediment output from each study catchment. The mean level of fine-grained sediment storage in the main channel system is equivalent to 38% (Pang) and 21% (Lambourn) of the respective mean annual suspended sediment yields of the two catchments. The estimated sediment delivery ratio for both study catchments is ca. 1%. © 2006 Elsevier B.V. All rights reserved.
Keywords: 137CS MEASUREMENTS; CHANNEL STORAGE; SEDIMENT BUDGETS; SEDIMENT DELIVERY RATIO; SEDIMENT SOURCES; SEDIMENT STORAGE; SOIL EROSION; SUSPENDED SEDIMENT YIELD